RESEARCH REGARDING OIL SEEDS CROPS DEVELOPMENT IN ROMANIA IN THE EU CONTEXT - Popescu, Agatha (Economics of Agriculture, 2012)
The paper aimed to present the dynamics of sunflower, soybean and rape cultivated area, yield and production in Romania in the period 1990-2009 and established the 2012-2015 forecast. In this respect, the statistical data have been processed based on fixed indices and average annual growth rate. Romania is an important oilseeds producer contributing by 8.22% to the EU-27 production. In 2009, Romania oilseeds production counted for 1,764 thou tons of which sunflower seeds 62.24 %, rapeseeds 32.29 % and 5.47 % soy beans. In 2015, it is forecast as oilseeds production to reach 7,850 thou tons, of which 73.84 % sunflower seeds and 25.26 % rapeseeds.